Вы находитесь на странице: 1из 2

Equations for cumulants

RUI LI
January 2015

1 Source Function p(1,2)s


Let

x = hhL{σi† }(λ, t), σj (t)ii


y = hhL{a}(λ, t), σj (t)ii
z = hhL{σi }(λ, t), σj (t)ii

−a(t) ρeg (t) (i = j)
α1 = hhai (t), σj (t)ii =
ρee,eg (t) − a(t) ρeg (t) (i 6= j)
−ρeg (t)2

(i = j)
α2 = hhσi (t), σj (t)ii =
ρeg,eg (t) − ρeg (t)2 (i 6= j)

a(t) − ρeg (t) ρge (t) (i = j)
α3 = hhσi† (t), σj (t)ii =
ρeg,ge (t) − ρeg (t) ρge (t) (i 6= j)

then the algebraic equation system on Page 3 of former attachment becomes


γ

 (λ + 2 + Γ − i∆) x = α3 − 2 i Ω y
(λ + γ + 2 Γ) y = α1 + i Ω z − i Ω x
(λ + γ2 + Γ + i∆) z = α2 + 2 i Ω y

In principle, we can solve for all x,y,z from above. Since here we only care
about hhL{σi† }(λ, t), σj (t)ii, I only show the solution of x which is

x = hhL{σi† }(λ, t), σj (t)ii



−4 i Ω γ + 2 (Γ + λ) α1 + 2 (γ + 2 Γ + λ) (γ + 2 (Γ + i∆ + λ)) α3 + 8 Ω2 (α2 + α3 )
=  
2
(γ + 2 Γ + λ) 4 ∆2 + (γ + 2 (Γ + λ)) + 8 (γ + 2 (Γ + λ)) Ω2

= hhσj† (t), L{σi }(λ, t)ii∗ (1)

Plug it into the definition of source function in Fourier space to get

1
℘2 (1)  † †

p(1)s = N hhL{σ }(λ, t), σ (t)ii + hhσ (t), L{σ }(λ, t)ii (2)

i j j i
~2

i=j
℘2 (2)  
p(2)s = 2N hhL{σi† }(λ, t), σj (t)ii + hhσj† (t), L{σi }(λ, t)ii (3)

~ i6=j

2 Source Function p(1,2)ret


Let
x = hhL{σi }(λ, t), σj† (t)ii
y = hhL{a}(λ, t), σj† (t)ii
z = hhL{σi† }(λ, t), σj† (t)ii

† 1 − a(t) − ρeg (t)ρge (t) (i = j)
β1 = hhσi (t), σj (t)ii =
ρeg,ge (t) − ρeg (t)ρge (t) (i 6= j)

ρge (t) − a(t) ρge (t) (i = j)
β2 = hhai (t), σj† (t)ii =
ρee,ge (t) − a(t) ρge (t) (i 6= j)
−ρge (t)2

† † (i = j)
β3 = hhσi (t), σj (t)ii =
ρge,ge − ρge (t)2 (i 6= j)
then the algebraic equation system on Page 4 of former attachment becomes
γ

 (λ + 2 + Γ + i∆) x = β1 + 2 i Ω y
(λ + γ + 2 Γ) y = β2 + i Ω x − i Ω z
(λ + γ2 + Γ − i∆) z = β3 − 2 i Ω y

In principle, we can solve for all x,y,z from above. Again, here we only care
about hhL{σi }(λ, t), σj† (t)ii, I only show the solution of x which is

x = hhL{σi }(λ, t), σj† (t)ii


2 (((γ + 2 Γ + λ) (γ + 2 (Γ − i∆ + λ)) + 4 Ω2 ) β1 + 2 Ω ( i (γ + 2 (Γ − i∆ + λ)) β2 + 2 Ω β3 ))
=
(γ + 2 Γ + λ) (4∆2 + (γ + 2 (Γ + λ))2 ) + 8 (γ + 2 (Γ + λ)) Ω2
= hhσi (t), L{σj† }(λ, t)ii∗ (4)
Plug it into the definition of source function in Fourier space to get

℘2 (1)  † †

p(1)ret = N hhL{σ }(λ, t), σ (t)ii − hhσ (t), L{σ }(λ, t)ii (5)

i j i j
~2

i=j

p(2)ret =0 (6)
For the detailed derivations of α0 s and β 0 s, please refer to the former attach-
ment named ”superradiance” or AAMO paper. Here I only give the results for
simplicity.